DETERMINATION OF OPTIMUM DAM LOCATION IN AL-ABEDH BASIN UTILIZING REMOTE SENSING AND GEOGRAPHICAL INFORMATION SYSTEM TECHNIQUES - & et al., Jawad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The hard environmental factors of AL-Abedh basin region forced the native tribes to make multitude migrations in it around the year seeking for water and pasture lands . Existence of sufficient water supplement will settle these tribes down and enhancing their eco system. The real capability of GIS software to be a decisions making support tool or operations management assistant mean came from its ability of data integration and information analysis. This capability was invested in this research to determine the optimum location of a dam that confine huge amount of water in its lake which can be used to provide water for drinking, pasture irrigation and land reclamation along the valley banks, and hydroelectricity power generation. In this location one dam with two possible heights could be constructed with a medium to few permeability reservoir soil behind it having 77.781 km2 and 1039.306 km2 areas respectively.